Oral Health-Related Quality of Life in Patients With Chronic Respiratory Diseases—Results of a Systematic Review - Li, Simin; Ning, Wanchen; Wang, Wei; Ziebolz, Dirk; Acharya, Aneesha; Schmalz, Gerhard; Zhao, Jianjiang; Huang, Shaohong; Xiao, Hui (Frontiers in Medicine, 2022)
Background: This systematic review evaluates the oral health-related quality of life (OHRQoL) of patients with chronic respiratory diseases. Methods: A systematic literature search was performed based on the PubMed, Medline, Web of Science, and Scopus, using the search terms: “oral health-related quality of life” and “respiratory disease” or “lung” and “oral health-related quality of life.” Full-text articles published until June 30, 2021 and reporting any OHRQoL measurement in children or adults with a chronic respiratory disease or condition were included and analyzed qualitatively. Results: A total of seven out of 44 studies were included, of which four studies examined adults and three studies investigated children. The respective diseases were chronic obstructive pulmonary disease (COPD) (n = 2), sleep apnea (n = 2), severe asthma (n = 1), cystic fibrosis (n = 1), and lung transplantation (n = 1). Four studies confirmed a worse OHRQoL in the respiratory diseased group compared to healthy controls. The overall OHRQoL was reduced in the included studies. Oral health, health-related quality of life, and disease-related parameters were rarely examined with regard to OHRQoL. Conclusion: Patients with chronic respiratory diseases show a reduced OHRQoL. Oral health should be fostered in these individuals to support their OHRQoL.